Positive Politeness Strategies Used by Parents in Peppa Pig Official YouTube Channel - Natasha Ayalus Yoan Yola Yolanda; Barli Bram (Hasanuddin University, 2022)
Parents are the first ones responsible for their children’s speech. Bad and good children’s speech behavior in society would be considered the results of their parents’ teachings. This research was conducted to analyze this phenomenon by exploring the positive politeness used by parents while communicating in front of their children. It showed how parents construct their speech to exemplify good speech behavior to their children. This research used qualitative research, specified to content analysis method to analyze the data. The data were collected from the video entitled “Peppa Pig Official Channel, Peppa Pig Adds Pineapple in Her Pizza” from Peppa Pig Official YouTube Channel. The results showed that the most strategy used was the ‘include both speakers and hearers in the activity’ which appeared in 36 out of 319 utterances. It showed Daddy Pig’s and Mommy Pig’s efforts to promote the politeness of appreciating others’ existence through their speech to their children. Furthermore, all the positive politeness strategies were used by Daddy Pig and Mommy Pig as the parents in Peppa Pig Video. Therefore, this video was recommended for parents to see how they can construct their language politely while speaking with their children. It will help children to get used to speaking politely and appropriately.